Role of cholecystokinin and central serotonergic receptors in functional dyspepsia - Chua, Andrew Seng Boon (Baishideng Publishing Group Co., Limited, 2006)
Symptoms of functional dyspepsia are characterized by upper abdominal discomfort or pain, early satiety, postprandial fullness, bloating, nausea and vomiting. It is a chronic disorder, with symptoms more than 3 mo per year, and no evidence of organic diseases. Dysfunctional motility, altered visceral sensation, and psychosocial factors have all been identified as major pathophysiological mechanisms. It is believed that these pathophysiological mechanisms interact to produce the observed symptoms. Dyspepsia has been categorized into three subgroups based on dominant symptoms. Dysmotility-like dyspepsia describes a subgroup of patients whose symptom complex is usually related to a gastric sensorimotor dysfunction. The brain-gut peptide cholecystokinin (CCK) and serotonin (5-HT) share certain physiological effects. Both have been shown to decrease gastric emptying and affect satiety. Furthermore the CCK induced anorexia depended on serotonergic functions probably acting via central pathways. We believe that abnormalities of central serotonergic receptors functioning together with a hyper responsiveness to CCK or their interactions may be responsible for the genesis of symptoms in functional dyspepsia (FD).